Demonstration of a Practical Cooling Storage System for Lithium-Ion Batteries with Trimethylolethane (TME) Hydrate for EV - Leo Kamiya; Ryo Koyama; Yuta Arai; Ryo Ohmura (Energies)
Lithium-ion batteries are required to equip the cooling system for high power performance, quick charge, and safety. Trimethylolethane (TME) hydrate is known as phase change material (PCM), a cooling medium that offers large dissociation heat and 30 °C form/dissociation temperature under atmospheric pressure. This study demonstrates the design of a practical cooling system with TME hydrate. This cooling method involves cooling outdoor air through water contact, exchanging heat between the cooled outdoor air and the aqueous solution of TME hydrate, exchanging heat from the resulting TME hydrate with a refrigerant, and finally supplying the processed refrigerant to the cooling LIB. Koyama et al. conducted a study on the physical properties of TME hydrate. They measured equilibrium temperatures and dissociation heats of TME mass fractions from 0.20 to 0.80. Their findings revealed that at a mass fraction of 0.60, the system reached its highest equilibrium temperature of 29.6 °C, and the dissociation heat peaked at 190.1 kJ/kg. This cooling system employed TME hydrate. These results underscore the potential of TME hydrates in energy-efficient cooling systems and demonstrate that they are suitable for lithium-ion battery cooling systems.